A bibliometric review of the STEAM approach in university education 2010-2022 - Tapullima-Mori, Calixto (2023)
Introduction: The present study sought to explore and characterize the scientific production of the STEAM approach in university education. Method: The bibliometric design study that analyzed the SCOPUS database, used the VOSviewer program, analyze search and the PRISMA methodology. Results: The STEAM approach has been developed in the field of university education since 2010; however, its continuity between 2012 and 2014 was affected. Countries such as the United States and Spain are leaders in scientific production in high-impact journals (Q1); in addition, the results reflect the adequate applicability of the STEAM approach in the university context. Discussion: The studios pose a marked line of studies such as social sciences and engineering, as it allows the development of diverse skills in the students and promotes the solution of conflicts and innovation; however, the results must be analyzed with caution.